The Effectiveness of Using the Quiz Team Method with Interactive Media to Enhance Collaboration and Student activity in VII Grade of MTs Negeri 3 Cilacap - Mahmudin Mahmudin (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This study aims to determine the effectiveness of the  quiz team method with interactive media in enhancing the collaboration and student activity in aljabar material. This research is a classroom action research with 20 students as the research subjects. This study consisted of 2 cycles that each cycle has 2 times of meetings. The utilized instruments were questionnaire sheet, interview sheet, and observation sheet. The data analysis technique uses descriptive qualitative. The results of the analysis show that: 1) the  quiz team method assisted by effective interactive media to enhance  collaboration and student activity; 2) collaboration and student activity in the first cycle showed quite good categories with an average score of 2,50 and 2,35; 3) collaboration and student activity  in the second cycle showed good categories with an average score of 3,20 and 3,00.